Instilling the Dangers of Radicalism and Terrorism and Love for the Motherland in Citizenship Education - Nazla Khairani (International Journal of Students Education, 2024)
The threat of extremism and terrorism continues to increase in Indonesia. Groups that are vulnerable to this extremist movement include elementary and high school students, campus academics and the general public. This preventive action can be implemented in various ways, including building community resilience. The aim of this research is to instill the dangers of radicalism and terrorism and foster a sense of patriotism in students’ civics education. The research method used is literature review by using analytics to describe the phenomenon of extremist movements and terrorist acts in Indonesia and analyzing early prevention efforts that the government can take. Research results: There are two patterns of spread of radicalism in Indonesia, namely first, through NGOs (Non-Government Organizations) or NGOs (Non-Governmental Organizations). The development of state defense awareness to combat several of the above phenomena has not been implemented comprehensively by state administration institutions, including the use or utilization of infrastructure to develop state defense awareness initiated by ministries and organizations such as state defense. Therefore, citizenship education has a very important role in efforts to combat the spread of extremism and terrorism in Indonesia. Because, through this education, the basic cultivation of nationalism and love of the country can be instilled in students who are a group that is most likely to be the target of communist indoctrination which means progressive. Conclusion: to instill the dangers of radicalism and terrorism in students can be done by instilling a spirit of nationalism and love for the country; enriching a moderate, open and tolerant religious vision ; building self-confidence by always being alert to provocation, incitement and forms of terrorist recruitment both in society and in cyberspace; and building networks with peace communities, both offline and online, to increase insight and knowledge.